What are favouring conditions for the implementation of innovative projects in Community-Led Local Development (CLLD) approaches? - Kim Pollermann; Lynn-Livia Fynn; Stefan Schwarze (ZBW - Leibniz Information Centre for Economics, 2021)
Fostering innovation-driven regional development has become a major priority for public policy. Thus innovation is a crucial issue in Rural Development Programmes (RDP) to overcome challenges like economic development and demographic change. One part of RDP funded by the European Union, which explicitly addresses innovation, is LEADER: a bottom-up-oriented, participatory approach which relies on cooperation between local actors in the sense of a Community-led local development (CLLD). Stakeholders of different institutions and origins come together in a Local Action Group (LAG) to decide on the projects to be financed. Previous research provides evidence that rural communities are innovative when they have the necessary space and power to act. There is, however, little knowledge about the factors, which are crucial for the power to act, and about the policy framework that provides the necessary space in CLLD-context. The aim of the paper is hence to identify factors, which influence the implementation of innovative projects. Our analysis builds on surveys among LAG-managers, LAG-members and beneficiaries in 115 LEADER areas in four federal states in Germany (Hesse, Lower-Saxony, North Rhine-Westphalia and Schleswig-Holstein). Since the explanatory is a dummy variable we used logit models for the analysis. Overall, 56% of the beneficiaries classified their own project as innovative. There are, however, large differences between the different federal states. Our econometric results suggest that origin of the project idea and the type of beneficiary significantly influence the likelihood of innovation. The expectation that heterogeneity fosters innovative ideas is not supported by our analyses.Fostering innovation-driven regional development has become a major priority for public policy. Thus innovation is a crucial issue in Rural Development Programmes (RDP) to overcome challenges like economic development and demographic change. One part of RDP funded by the European Union, which explicitly addresses innovation, is LEADER: a bottom-up-oriented, participatory approach which relies on cooperation between local actors in the sense of a Community-led local development (CLLD). Stakeholders of different institutions and origins come together in a Local Action Group (LAG) to decide on the projects to be financed. Previous research provides evidence that rural communities are innovative when they have the necessary space and power to act. There is, however, little knowledge about the factors, which are crucial for the power to act, and about the policy framework that provides the necessary space in CLLD-context. The aim of the paper is hence to identify factors, which influence the implementation of innovative projects. Our analysis builds on surveys among LAG-managers, LAG-members and beneficiaries in 115 LEADER areas in four federal states in Germany (Hesse, Lower-Saxony, North Rhine-Westphalia and Schleswig-Holstein). Since the explanatory is a dummy variable we used logit models for the analysis. Overall, 56% of the beneficiaries classified their own project as innovative. There are, however, large differences between the different federal states. Our econometric results suggest that origin of the project idea and the type of beneficiary significantly influence the likelihood of innovation. The expectation that heterogeneity fosters innovative ideas is not supported by our analyses.
Conference: ,,Structural change in rural and urban economies“ - 11th summer conference of the German-speaking section (GfR) of the European Regional Science Association (ERSA), 2-3 July 2020, Thünen Institute, Braunschweig
Keywords: R1; 330; Innovation; Rural development; LEADER; evaluation